The Effect of Management Effectiveness and FFB Weighing Efficiency at the Palm Oil Mill Weighing Bridge on the Acceleration of FFB Purchases at PT Anj Agri Binanga - Djurmiani Nasution; Tri Inda Fadhila Rahma; Kusmilawaty (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine the analysis of the efficiency of the use of technology on the weighbridge of palm oil mills on the speed of purchasing FFB at PT ANJ Agri Binanga both partially and simultaneously. This research method is with a quantitative approach. Multiple regression analysis techniques with variables of effectiveness, efficiency and acceleration of purchases. The results of this study indicate that Effectiveness that meets the